2019
DOI: 10.5455/umj.20190813065101
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck cancers in geriatric population in a tertiary care institute in India: Lessons learnt

Abstract: This is an Open Access article distributed under the terms of Creative Commons Attribution Non-Commercial License, which permits unrestricted non-commercial use, distribution, and reproduction in any area, original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Head and neck cancer (HNC) is the sixth most prevalent type of cancer globally, and it is especially common in some of the less developed nations. 1,2 Currently, standard treatments for HNCs are surgery and radiotherapy with or without chemotherapy, which are always associated with side effects during or after treatment. Oral mucositis and dry mouth are the most frequent side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer (HNC) is the sixth most prevalent type of cancer globally, and it is especially common in some of the less developed nations. 1,2 Currently, standard treatments for HNCs are surgery and radiotherapy with or without chemotherapy, which are always associated with side effects during or after treatment. Oral mucositis and dry mouth are the most frequent side effects.…”
Section: Introductionmentioning
confidence: 99%
“…According to the need of older person's medical, psychosocial and functional capability to develop a coordinated integrated plan for treatment and follow up [13]. Treatment can be tailored by on- [ 20] shown two third of elderly patients of head and neck cancer presented in advanced stage of decrease western population [18].…”
Section: Background Introductionmentioning
confidence: 99%
“…Huang., et al [23] shown cancer were commonest site followed by oral cavity. Median age in our study was 68 years, while study done by Patil., et al [24] was 75 years and Tiwari., et al was 70 years [18]. Study done by Tiwari., et al shown 75% of patients presented with stage III and IV disease [18].…”
Section: Background Introductionmentioning
confidence: 99%
See 2 more Smart Citations